Pengaruh Program Keluarga Harapan ( PKH ) terhadap Prestasi Belajar Siswa di Madrasah Ibtidaiyah ( MI ) Ã¢â‚¬ËœUlumiyah Semanding Tertek Pare Kediri - Umar, Mudawamah (INOVATIF: Jurnal Penelitian Pendidikan, Agama dan Kebudayaan, 2016)
Problem: Is there any influence between the Family Hope Program (PKH) with student achievement at Government Elementary School (MI) 'Ulumiyah Semanding Tertek Pare Kediri district. Research variables: in this study, there are two variables, namely the independent variable / PKH ie independent and dependent variable / dependent that achievement. Method and Instrument: The research method is to use questionnaires, documentation, observation and interviuw, while the instrument using questionnaires guidelines, documentation, observation and interviuw. Data analysis: Data from this study were tested using product moment correlation technique. Results: There was a correlation / relationship between PKH with student achievement in MI 'Ulumiyah Semanding Tertek Pare Kediri district. So, more often students get help PKH increasing student achievement in MI 'Ulumiyah Semanding Tertek Pare Kediri district.